2015
DOI: 10.1152/ajpendo.00205.2014
|View full text |Cite
|
Sign up to set email alerts
|

11β-Hydroxysteroid dehydrogenase type 1 shRNA ameliorates glucocorticoid-induced insulin resistance and lipolysis in mouse abdominal adipose tissue

Abstract: . 11␤-Hydroxysteroid dehydrogenase type 1 shRNA ameliorates glucocorticoid-induced insulin resistance and lipolysis in mouse abdominal adipose tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 52 publications
1
32
0
1
Order By: Relevance
“…Interestingly, liver-specific 11BHSD1-KO did not protect the mice from adverse liver effects, suggesting the importance of 11BHSD1 expression in the adipose tissue in mediating negative metabolic effects on the liver (73). In another study, corticosterone treatment increased 11BHSD1 expression in adipose tissue of mice, and 11BHSD1 knockdown by shRNA attenuated GC-induced lipolysis and ameliorated insulin resistance in adipocytes (74). Adipose tissue-specific overexpression of 11BHSD1 leads to increased corticosterone content in fat tissue and associates to signs of the metabolic syndrome with visceral obesity, worsened by a high-fat diet, pronounced insulinresistant diabetes, hyperlipidaemia and hyperphagia despite hyperleptinaemia (75).…”
Section: European Journal Of Endocrinologymentioning
confidence: 97%
“…Interestingly, liver-specific 11BHSD1-KO did not protect the mice from adverse liver effects, suggesting the importance of 11BHSD1 expression in the adipose tissue in mediating negative metabolic effects on the liver (73). In another study, corticosterone treatment increased 11BHSD1 expression in adipose tissue of mice, and 11BHSD1 knockdown by shRNA attenuated GC-induced lipolysis and ameliorated insulin resistance in adipocytes (74). Adipose tissue-specific overexpression of 11BHSD1 leads to increased corticosterone content in fat tissue and associates to signs of the metabolic syndrome with visceral obesity, worsened by a high-fat diet, pronounced insulinresistant diabetes, hyperlipidaemia and hyperphagia despite hyperleptinaemia (75).…”
Section: European Journal Of Endocrinologymentioning
confidence: 97%
“…These studies demonstrated that systemic and/or local GC excess is associated with reduced adipose tissue insulin signaling and significant glucose and lipid homeostasis imbalance [10,11,16,28] . The alterations in insulin signaling pathway include reduced adipose tissue IRS-1 Tyr and PKB Ser/Thr phosphorylation [10,11,16] . By blocking/reducing the 11β-HSD-1 enzyme activity with pharmacological [28] genetic (knockout) [11] or molecular (knockdown) [16] tools, obese mice made by prolonged GC exposure or high-fat diet become partially prevented from the glucose and lipid imbalance, suggesting a negative impact of elevated local GC abundance for adequate adipose tissue biology.…”
Section: Research Highlightmentioning
confidence: 99%
“…GCs modulate several processes in the adipose tissue such as adipocyte differentiation/adipogenesis [9][10][11][12][13] , and exert both anabolic (e.g., lipogenesis) and catabolic (e.g., lipolysis) [10][11][12][13][14][15][16] functions, depending on the fat depot evaluated and stage of adipocyte differentiation/maturation. It is consensually accepted that GCs promote adipogenesis and/or lipogenesis (visceral adipose tissue) and lipolysis (subcutaneous adipose tissues), which correspond with clinical features of abdominal obesity and limited subcutaneous fat on the extremities in patients with Cushing's syndrome [4] .…”
Section: Research Highlightmentioning
confidence: 99%
See 2 more Smart Citations